Islamic Education for Environmental Conservation in the Hadith - Mudaris, Hudan; Musaropah, Umi; Suprianto, Agus; Dhiyauddin, Muhammad; Muthmainnah, Muthmainnah (Universitas Cokroaminoto Yogyakarta, 2024)
This study explores a series of hadiths related to environmental conservation. From there, Islamic education can be proposed that provides environmental insight for people throughout their lives. The search for this hadith is based on software and a hadith website, then its sanad is analyzed thematically. Islamic education with an environmental conservation perspective thus respects biodiversity for all parties in this universe in a sustainable manner so that it can be felt by the next generation.